Swept-Source Optical Coherence Tomography Detecting Intraoperative Acute Descemet's Fold Formation - Ichioka, Yu (Case Rep Ophthalmol, 2016)
BACKGROUND: To present an intraoperative acute Descemet's fold formation using swept-source optical coherence tomography (SS-OCT) imaging. CASE REPORT: A 67-year-old man complaining of reduced visual acuity in the left eye. A 25-gauge pars plana vitrectomy combined with phacoemulsification cataract surgery was performed to remove the vitreomacular traction. When hydro-sealing was performed, striae rapidly spread in the cornea. SS-OCT B-scan images performed on postoperative day 1 revealed a wavy Descemet's membrane that might correspond to Descemet's folds. Pairs of hypo- and hyperreflective narrow lesions running from the wavy Descemet's membrane to almost half of the thickness of the whole cornea were observed. En face OCT imaging clearly showed the stromal fold, which continuously spread from the Descemet's fold. CONCLUSION: The stromal fold might be due to the focal bulge of the stroma posteriorly caused by the rapid volume increase of the stroma which could push Descemet's membrane posteriorly, thereby forming a wavy Descemet's membrane layer.